Undesirable Output in Environmental Efficiency: Evidence from ASEAN Countries - Kusumawardhani, Hapsari Ayu (Signifikan: Jurnal Ilmu Ekonomi, 2025)
Research Originality: This study enriches the environmental efficiency literature by applying a DEA model that considers undesirable outputs, to produce more comprehensive and accurate efficiency estimates, especially in the context of the ASEAN region Research Objectives: To evaluate and compare the relative environmental efficiency of ASEAN countries using the Data Envelopment Analysis (DEA) method Research Methods:  This study applies the DEA approach to measure environmental efficiency in ASEAN countries from 2000 to 2022, using population and industry as inputs, and GDP and CO2 emissions as outputs Empirical Results: The findings indicate variations in environmental efficiency among ASEAN countries, reflecting differences in industrial policies and levels of economic development. Singapore emerges as the most efficient country, while Indonesia is identified as one of the ASEAN countries that needs to focus on improving its environmental efficiency. Implications: The research results show significant variation in environmental efficiency across ASEAN countries. This finding emphasizes the importance of formulating development policies that are not solely oriented toward economic growth but also address resource efficiency and emission reduction. Countries with low efficiency, such as Indonesia, need to develop more comprehensive, data-driven green transition strategies. JEL Classification: C31, G21, I32, O18 How to Cite:Kusumawardhani, H. A. (2025). Undesirable Output in Environmental Efficiency: Evidence from ASEAN Countries. Signifikan: Jurnal Ilmu Ekonomi, 14(2), 339-358. https://doi.org/10.15408/sjie.v14i2.45828.